Treatment of printed circuit board wastewater containing copper and nickel ions by fluidized-bed homogeneous granulation process - Quimada, Nathaniel E.
With the rapid advancement of evolution of world's informatics technology, the creation of electric and electronic equipment (EEE) is drastically increasing. Printed Circuit Boards (PCBs) are essential components in almost all EEE. However, the production of the PCBs produces wastewaters containing elevated concentrations of copper and nickel ions. If these metals ions are considered as major pollutants that affects human health and our environment. In this study, a system was proposed for the removal of copper and nickel ions from a synthetic wastewater by fluidized-bed homogeneous granulation process (FBHGP). The use of fluidized-bed reactor (FBR) evaluated the effects of different parameters, including initial operating pH, total carbonate loading and precipitant flow rate. The granules produced after the treatment were collected, dried, sieved and analyzed for the evaluation of their physical and chemical characteristics through SEM, XRD and EDX analyses. The optimum operating conditions was found to be at initial pH of 6.5, total carbonate loading of 17mM, precipitant flow rate of 15 mL/min; with the highest copper removal of 98% and copper granulation of 94%, nickel removal and nickel granulation of 80% and 72%, respectively. The granules collected at the optimum conditions were >0.42 mm diameter size and found to have presence of Cu²? Ni²? and O